2018
DOI: 10.3390/ph11010009
|View full text |Cite
|
Sign up to set email alerts
|

Improved Intranasal Retentivity and Transnasal Absorption Enhancement by PEGylated Poly-l-ornithine

Abstract: We reported that the introduction of polyethylene glycol (PEG) to poly-l-ornithine (PLO), which is an homopolymeric basic amino acid having absorption-enhancement ability, prolonged retention time in an in vitro inclined plate test, probably due to an increase in viscosity caused by PEGylation. The aim of the present study is to investigate whether the introduction of PEG chains to PLO improves intranasal retention and transnasal absorption in vivo. We performed intranasal administration experiments using PLO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…More drug can be delivered into brain if the Puerarin or Radix Puerariae Extract was combined with volatile oils. Moreover, application of bioadhesive dosage forms (like in situ gel delivery system and bioadhesive delivery system) [ 18 , 19 ] is helpful for the reduction of mucociliary clearance and prolonging of the drug residence time in the nasal cavity [ 20 ], which may also improve the drug distribution in brain.…”
Section: Discussionmentioning
confidence: 99%
“…More drug can be delivered into brain if the Puerarin or Radix Puerariae Extract was combined with volatile oils. Moreover, application of bioadhesive dosage forms (like in situ gel delivery system and bioadhesive delivery system) [ 18 , 19 ] is helpful for the reduction of mucociliary clearance and prolonging of the drug residence time in the nasal cavity [ 20 ], which may also improve the drug distribution in brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that PLO enhanced the uptake of FITC-insulin in cultured alveolar type II epithelial cells without cytotoxicity. 21) In addition, the hypoglycemic action of insulin was increased by pulmonary co-administration with PLO in an in vivo rat model. We also reported that PLO improved the in vivo nasal absorption of FD-4, and the improvement was dependent on its concentration.…”
Section: Cytotoxicity Of Plo On the Nasal Mucosamentioning
confidence: 99%
“…In terms of achieving the best outcomes for nasal drug delivery, enhancing residence times in the nasal cavity, and improving contact between the API and nasal epithelia or the olfactory nerve are important and common strategies in enhancing the degree of uptake, with modification of the dosage form (e.g., emulsion formulations) or incorporation with mucoadhesive agents (e.g., pectin and chitosan polymers) in the formulation. [ 14 ] We reasoned that supramolecular gels could be ideally suited to this application, given their potential for self‐healing and self‐assembly in situ, combined with their soft rheological properties. Although there has been rising interest in the use of responsive polymer gels for nasal drug delivery, [ 15 ] perhaps surprisingly, in spite of the attention focused on low‐molecular‐weight gelators, [ 3 ] they have not previously been explored in this regard.…”
Section: Introductionmentioning
confidence: 99%